2021
DOI: 10.21849/cacd.2021.00479
|View full text |Cite
|
Sign up to set email alerts
|

Narrative language development of Persian-English bilingual children attending an immersion preschool

Abstract: Purpose: This study aimed to provide a better understanding of the language development of bilingual children who attend a Persian immersion preschool in the United States, with a specific focus on their microstructural language skills derived from a story retell task.Methods: Participants included two groups of preschoolers: 14 Persian-English bilingual children who attended a Persian immersion preschool (2- through 5-years of age) and 16 monolingual English-speaking children who attended an English-only pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There are four studies concerned with the issue of language development for bilingual children. While Páez M. Mariela et al concluded that on average, children in the bilingual sample performed below average in both English and Spanish when compared to monolingual norms (Páez et al, 2007), research by Payesteh Bita and Finestack Lizbeth (2021) demonstrated that Persian-English bilingual children attending a Persian immersion preschool develop English at a level comparable to their monolingual Englishspeaking peers based on the language produced during the retelling of the story (Payesteh & Finestack, 2021) 2018) asserted that interdependence between languages can be modulated by the quality of classroom conversation and they suggested enhancing children's experiences of using social skills when explaining the meaning of words (Grøver et al, 2018). Farangi Mohamad Reza & Mehrpour Saeed (2022) have studied the association between television platform and social status with Preschool Minority Children's Persian Vocabulary Development.…”
Section: Researchers' Concerns About Language Development For Prescho...mentioning
confidence: 97%
“…There are four studies concerned with the issue of language development for bilingual children. While Páez M. Mariela et al concluded that on average, children in the bilingual sample performed below average in both English and Spanish when compared to monolingual norms (Páez et al, 2007), research by Payesteh Bita and Finestack Lizbeth (2021) demonstrated that Persian-English bilingual children attending a Persian immersion preschool develop English at a level comparable to their monolingual Englishspeaking peers based on the language produced during the retelling of the story (Payesteh & Finestack, 2021) 2018) asserted that interdependence between languages can be modulated by the quality of classroom conversation and they suggested enhancing children's experiences of using social skills when explaining the meaning of words (Grøver et al, 2018). Farangi Mohamad Reza & Mehrpour Saeed (2022) have studied the association between television platform and social status with Preschool Minority Children's Persian Vocabulary Development.…”
Section: Researchers' Concerns About Language Development For Prescho...mentioning
confidence: 97%
“…Other language immersion variants are total, partial, and two-way immersion [5]. These diverse language immersion variants have widely implemented and brought positive impact to language learners, be it the aspect of linguistic [7] and cognitive [8], [9], language use [10] and proficiency [11], [12], phonological awareness [13], faster language development [14] in a shorter time and better result [2], provides a unique contribution to receptive and expressive language skills [15], multilingual attitude [16], multicultural identity [17], [18], and intercultural competence [19].…”
Section: Introductionmentioning
confidence: 99%